2011
DOI: 10.1055/s-0030-1260764
|View full text |Cite
|
Sign up to set email alerts
|

N-Aryl-2-nitrosoanilines as Intermediates in the Two-Step Synthesis of Substituted 1,2-Diarylbenzimidazoles from Simple Nitroarenes

Abstract: N-Aryl-2-nitrosoanilines, easily available from reaction of nitroarenes with anilide anions, undergo base-promoted condensation reaction with substituted benzyl aryl sulfones, furnishing 1,2-diaryl-1H-benzimidazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The vicinal position of nucleophilic amino—and strongly electrophilic nitroso—groups makes these compounds very interesting starting materials for domino reactions with properly equipped dipolar partners, leading to a variety of heterocyclic systems. It was already shown that reactions of title compounds with comparatively acidic sulfones (Scheme , route 1) or acetates and phosphonoacetates (Scheme , route 2) are efficient ways of synthesis of benzimidazoles and quinoxalin‐2(1 H )‐ones . Here, we would like to report a new reaction of N ‐aryl‐2‐nitrosoanilines with alkylated derivatives of cyanoacetic esters furnishing quinoxalin‐2(1 H )‐one‐4 N ‐oxides in moderate to excellent yields.…”
Section: Introductionmentioning
confidence: 95%
“…The vicinal position of nucleophilic amino—and strongly electrophilic nitroso—groups makes these compounds very interesting starting materials for domino reactions with properly equipped dipolar partners, leading to a variety of heterocyclic systems. It was already shown that reactions of title compounds with comparatively acidic sulfones (Scheme , route 1) or acetates and phosphonoacetates (Scheme , route 2) are efficient ways of synthesis of benzimidazoles and quinoxalin‐2(1 H )‐ones . Here, we would like to report a new reaction of N ‐aryl‐2‐nitrosoanilines with alkylated derivatives of cyanoacetic esters furnishing quinoxalin‐2(1 H )‐one‐4 N ‐oxides in moderate to excellent yields.…”
Section: Introductionmentioning
confidence: 95%
“…IR (thin film): 3232, 3023, 2930, 1600, 1571, 1532, 1506 cm -1 . 6, 159.1, 157.2, 135.1, 122.8 (d, 3 J C,F = 7.9 Hz), 119.5 (d, 4 N-(5-Nitropyridin-2-yl)-4-(trifluoromethyl) (d, J = 8.5 Hz, 2 H, H-3′,5′ C 6 H 4 ), 7.71 (d, J = 8.5 Hz, 2 H, H-2′,6′ C 6 H 4 ), 7.01 (d,J = 9.3 Hz,1 H,. Hz, 1 H, H-6 Py), 8.31 (dd, J = 9.3, 2.8 Hz, 1 H, H-4 Py), 7.71 (d, J = 8.9 Hz, 2 H, H-3′,5′ C 6 H 4 ), 7.53 (d, J = 8.9 Hz, 2 H, H-2′,6′ C 6 H 4 ), 6.92 (d,J = 9.3 Hz,1 H,.…”
Section: -Methyl-n-(5-nitrosopyridin-2-yl)aniline (3b)mentioning
confidence: 99%
“…1 H NMR (400 MHz, DMSO-d 6 ): δ = 9.78 (br s, 1 H, NH), 8.94 (d, J = 2.8 Hz, 1 H, H-6 Py), 8.31 (dd, J = 9.3, 2.8 Hz, 1 H, H-4 Py), 7.70 (dd, J = 7.8, 1.5 Hz, 1 H, H-3′ C 6 H 4 Cl), 7.55 (dd, J = 8.0, 1.3 Hz, 1 H, H-6′ C 6 H 4 Cl), 7.39 (ddd, J = 6.7, 8.0, 1.5 Hz, 1 H, H-5′ C 6 H 4 Cl), 7.27 (ddd, J = 7.8, 6.7, 1.3 Hz, 1 H, H-4′ C 6 H 4 Cl), 6.88 (d,J = 9.3 Hz,1 H,. 8, 145.9, 136.4, 135.6, 133.0, 129.9, 128.3, 127.7, 127.3, 126.9, 109. (d, J = 8.0 Hz, 1 H, H-3′ C 6 H 4 ), 7.58 (dd, J = 8.1, 1.2 Hz, 1 H, H-6′ C 6 H 4 ), 7.43 (ddd, J = 8.0, 7.6, 1.2 Hz, 1 H, H-4′ C 6 H 4 ), 7.32 (ddd, J = 8.1, 7.6, 1.4 Hz, 1 H, H-5′ C 6 H 4 ), 7.15 (dd, J = 9.2, 2.0 Hz, 1 H, H-4 Py), 6.79 (d,J = 9.2 Hz,1 H,. 0, 160.0, 158.3, 135.1, 129.6, 128.7, 127.6, 127.5, 127.2, 120.1, 109.4…”
Section: -Chloro-n-(5-nitropyridin-2-yl)aniline (2h)mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter, bearing two differently polarized groups, proved to be valuable starting materials in the synthesis of various nitrogen heterocycles. [3][4][5][6][7][8] An attractive transformation of 2-nitrosodiarylamines appeared to be their smooth reaction with triphenylphosphine, first published in 2014, 9 leading to 2-(arylamino)aryliminophosphoranes via a Cadogan-type reaction. These turned out to be versatile and stable equivalents for 1-aryl-1,2-arylenediamines; they reacted with isocyanates, 9 nitrous acid, 10 CS 2 11 and CO 2 12 furnishing 2-aminobenzimidazoles, benzotriazoles, 2-thiobenzimidazoles and 2-benzimidazolones respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%